2016
DOI: 10.15277/bjd.2016.077
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes should not dissuade arteriovenous fistula formation

Abstract: Background: Fistula maturation is a complex multifactorial process with the effect of diabetes on vessel augmentation during fistula formation remaining unclear. Variation in results has reflected in a range of clinical practice with regard to patient selection and fistula formation and so requires more study. The aim of our study was to compare outcomes of diabetic and non-diabetic patients undergoing formation of a new upper limb arteriovenous fistula (AVF) to assess whether diabetes has a prognostic effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…On the contrary, many authors have stated that diabetes is associated with a higher risk of AVF failure. In this regard, Jeong et al reported higher mortality rates and worse AVF patency rates in diabetic patients vs. non-diabetic ESRD patients undergoing hemodialysis (11). In a previously reported systematic review, there is an increased risk of AVF failure in ESRD patients with diabetes (12).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, many authors have stated that diabetes is associated with a higher risk of AVF failure. In this regard, Jeong et al reported higher mortality rates and worse AVF patency rates in diabetic patients vs. non-diabetic ESRD patients undergoing hemodialysis (11). In a previously reported systematic review, there is an increased risk of AVF failure in ESRD patients with diabetes (12).…”
Section: Discussionmentioning
confidence: 99%
“…Study by Ahmadi involving 400 patients reported that diabetes did not increase the risk of early AVF failure, while patients with a previous history of hypertension had a lower risk of AVF failure [20]. Gordon concluded that diabetic patients should not be discouraged from undergoing AVF formation, as they have comparable outcomes to non-diabetic patients, with AVF remaining the optimal access for dialysis [21].…”
Section: Discussionmentioning
confidence: 99%